Designed and Implementation of Grid Connected Converter System for Exercise Bike - Benjanarasut., Jirawut (Thailand Electrical Engineering Journal (TEEJ), 2025)
This paper proposed an experimental design and implementations of 250 VA grid connected converter system for an exercise bike that consist of an exercise bike, coupling with a generator and a grid connected converter system. The converter system has two main parts. The first part is a synchronous boost converter that adjusts viscosity of an exercise bike generator via control synchronous boost converter current. It was applied to an analog comparator module of STM32F334R8 microcontroller. The second part is a grid tie inverter that transfers energy from synchronous boost converter to grid. The experimental results verify the system can adjust the viscosity of an exercise bike equal to the conventional exercise bike and can deliver. module